2010
DOI: 10.1189/jlb.0210072
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue macrophages: their role in adipose tissue remodeling

Abstract: The adipose tissue secretes a large number of bioactive substances, adipocytokines, which may be involved in a variety of physiologic and pathologic processes. Unbalanced production of pro- and anti-inflammatory adipocytokines seen in visceral fat obesity contributes critically to the development of the metabolic syndrome. Evidence has accumulated indicating that obesity is associated with a state of chronic, low-grade inflammation, suggesting that inflammation may be a potential mechanism, whereby obesity lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
284
3
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 387 publications
(300 citation statements)
references
References 74 publications
4
284
3
9
Order By: Relevance
“…It has been shown in cellular models that fatty acid release from adipocytes is strongly stimulated by inflammation. 46 Animal studies have shown that the rate of fatty acid breakdown and insulin-induced lipogenesis was significantly higher in EF as compared with that in other fat depots. 47 The anatomic location of EF, without Cardiac adiposity and heart function in obesity B Gaborit et al any barrier to the adjacent myocardium, allows local paracrine interactions between EF and the myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown in cellular models that fatty acid release from adipocytes is strongly stimulated by inflammation. 46 Animal studies have shown that the rate of fatty acid breakdown and insulin-induced lipogenesis was significantly higher in EF as compared with that in other fat depots. 47 The anatomic location of EF, without Cardiac adiposity and heart function in obesity B Gaborit et al any barrier to the adjacent myocardium, allows local paracrine interactions between EF and the myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…There are reports to the effect that two types of macrophages, M1 and M2, are found in the adipose tissue suffering from macrophage infiltration, and that increases in M1 macrophages and the M1/M2 polarization of macrophages in the adipose tissue are closely involved in the onset and progression of insulin resistance (42)(43)(44)(45). Furthermore, Murakami et al reported that the PPAR␣ activation reduces macrophagederived inflammation in cultured adipocytes by suppressing the expression of Tnf through the inhibition of the nuclear factor-B (NF-B) signaling pathway (46).…”
Section: Discussionmentioning
confidence: 99%
“…Such dynamic histological changes observed in obese adipose tissue can be referred to as "adipose tissue remodeling" [10,17,18]. In this regard, recent evidence suggests that the interaction between mature adipocytes and stromal cells in adipose tissue plays a critical role in the regulation of adipocytokine production [18]. It is also known that, in addition to mature adipocytes, stromal cells are also important sources of certain adipocytokines such as tumor necrosis factor-α (TNFα).…”
mentioning
confidence: 99%
“…In other words, stromal cells change dramatically in number and cell type during the course of obesity. Such dynamic histological changes observed in obese adipose tissue can be referred to as "adipose tissue remodeling" [10,17,18]. In this regard, recent evidence suggests that the interaction between mature adipocytes and stromal cells in adipose tissue plays a critical role in the regulation of adipocytokine production [18].…”
mentioning
confidence: 99%